STRATEGI PENYELESAIAN KONFLIK PENGUASAAN LAHAN DALAM KAWASAN HUTAN DI DESA SOLAN KECAMATAN JARO PADA WILAYAH KPH TABALONG - Ikhlas, Muhammad Noor; Jauhari, Ahmad; Suyanto, Suyanto (Jurnal Hutan Tropis, 2024)
The Permanent Production Forest (HP) area in the Tabalong Regency area has an area of ± 44,759 ha which is a forest area in the Tabalong KPH management area. The administrative designation of this Forest Area is in Solan Village, Jaro District. In this area there are problems related to conflicts over land use and claims in locations whose status is still production forest areas. The Solan Village area which is within the Permanent Production Forest (HP) area covers an area of 4,161.2731 ha. In some areas, the Solan Village community uses the area for housing, public facilities and plantations. The area of Solan Village which is outside the forest area is 87,377 ha. The results of the questionnaire showed that 50% of respondents were not aware of the government's determination of forest area status and the boundaries of forest areas in their area. The community considers that the land belongs to them because it has been owned for generations. For this reason, it is necessary to carry out mapping regarding area control conflicts and re-arrangement of forest area boundaries in the Tabalong KPH area which aims to inventory land control problems and community rights to forest areas as well as safeguard and protect designated forest areas. Socialization and the presence of officers are important components to bring awareness and understanding to the community about forests and forest areas, so that conflicts over control of forest areas can be eliminated.